Exploring the effects of COLOSTRONONI on the mammalian gut microbiota composition - Duranti, Sabrina (PLoS One, 2019)
COLOSTRONONI is a dietary supplement consisting of bovine colostrum and Morinda citrifolia fruit (Noni). In this study, we tested the capability of COLOSTRONONI to influence gut microbiota composition using an in vivo evaluation in rats. Furthermore, we analyzed the effect of COLOSTRONONI on the systemic inflammatory responses as well as on the gut permeability of the animals. Altogether, our analyses supported the concept of COLOSTRONONI as a natural food supplement that doesn't affect (neither negatively nor positively) gut microbiota homeostasis in healthy conditions. Moreover, COLOSTRONONI highlighted a lower effect in the expression of genes coding for IL-10, Il-12 and TNF-α response allowing us to hypothesize an immunomodulatory activity of this dietary supplement.